Successive tendon injury in an in vivo rat overload model induces early damage and acute healing responses - Chainani, Pooja H.; Buzo Mena, Maria; Yeritsyan, Diana; Caro, Daniela; Momenzadeh, Kaveh; Galloway, Jenna L.; DeAngelis, Joseph P.; Ramappa, Arun J.; Nazarian, Ara (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Tendinopathy is a degenerative condition resulting from tendons experiencing abnormal levels of multi-scale damage over time, impairing their ability to repair. However, the damage markers associated with the initiation of tendinopathy are poorly understood, as the disease is largely characterized by end-stage clinical phenotypes. Thus, this study aimed to evaluate the acute tendon responses to successive fatigue bouts of tendon overload using an in vivo passive ankle dorsiflexion system. Methods: Sprague Dawley female rats underwent fatigue overloading to their Achilles tendons for 1, 2, or 3 loading bouts, with two days of rest in between each bout. Mechanical, structural, and biological assays were performed on tendon samples to evaluate the innate acute healing response to overload injuries. Results: Here, we show that fatigue overloading significantly reduces in vivo functional and mechanical properties, with reductions in hysteresis, peak stress, and loading and unloading moduli. Multi-scale structural damage on cellular, fibril, and fiber levels demonstrated accumulated micro-damage that may have induced a reparative response to successive loading bouts. The acute healing response resulted in alterations in matrix turnover and early inflammatory upregulations associated with matrix remodeling and acute responses to injuries. Discussion: This work demonstrates accumulated damage and acute changes to the tendon healing response caused by successive bouts of in vivo fatigue overloads. These results provide the avenue for future investigations of long-term evaluations of tendon overload in the context of tendinopathy.